Case of leucism in the spadenose shark, Scoliodon laticaudus (Müller and Henle, 1838) from Mangalore, Karnataka - Veena, S.; Sujitha, Thomas; Raje, S. G.; Raveendra, Durgekar (Indian Journal of Fisheries, 2011)
The present paper reports the first case of leucism in the spadenose shark, Scoliodon laticaudus from India. This report is based on the study of a single specimen of S. laticaudus caught by a commercial trawler off Mangalore coast. Photographs were taken and measurements recorded using vernier calipers. Partial reduction in pigmentation and no other morphometric differences were seen between the specimen studied and other normal spadenose sharks. Conclusion of leucism in the specimen was done based on the partial lack of integumentary pigments and normal eye colour.